Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have the following nested sum : $$\sum_{i=1}^{n}\sum_{j=1}^{i}\sum_{k=1}^{j}x = x+1$$

I don't have a clue how to solve this one, can somebody help me?

Thanks in advance. ${}{}$

share|improve this question
2  
I"m confused. Is it really supposed to be an $x$ on both sides here? –  Zev Chonoles Feb 24 '13 at 13:09
2  
This can't be correct. The right-hand side must depend on $n$, it seems to me. –  bubba Feb 24 '13 at 13:13
add comment

3 Answers 3

I will use the rules found on this page.

First, note that $x$ is not in the base or limit of any of the sums, so it can be "pulled out": $$x\sum_{i=1}^n\sum_{j=1}^i\sum_{k=1}^j 1= x+1$$

Work from inside to outside, simplifying the sum: $$\sum_{k=1}^j 1 = j$$ $$\sum_{j=1}^ij = \frac{i(i+1)}{2}=\frac{1}{2}\cdot\left(i^2 + i\right)$$ $$\sum_{i=1}^n\frac{1}{2}\cdot\left(i^2 + i\right) = \frac{1}{2}\left(\sum_{i=1}^ni^2+\sum_{i=1}^ni\right) = \frac{1}{2}\left(\frac{n(n+1)(2n+1)}{6} + \frac{n(n+1)}{2}\right)$$

Now we're done, and can plug back in:

$$\frac{x}{2}\left(\frac{n(n+1)(2n+1)}{6} + \frac{n(n+1)}{2}\right)=x+1$$

Now, solving for $x$: $$x\left(\frac{n(n+1)(2n+1)}{12} + \frac{n(n+1)}{4} - 1\right)=1$$ $$ \begin{align*} x &= \frac{1}{\left(\frac{n(n+1)(2n+1)}{12} + \frac{n(n+1)}{4} - 1\right)} \\ &= \frac{6}{n^3 + 3 n^2 + 2 n - 6} \end{align*} $$

share|improve this answer
    
Thank you very much, this made me understand it. –  Energyfellow Feb 24 '13 at 20:42
add comment

After a little rearrangement we have

$$\begin{align*} 1+\frac1x&=\sum_{i=1}^n\sum_{j=1}^i\sum_{k=1}^j1\\ &=\sum_{i=1}^n\sum_{j=1}^ij\\ &=\sum_{1=1}^n\frac{i(i+1)}2\\ &=\frac12\left(\sum_{i=1}^ni^2+\sum_{i=1}^ni\right)\\ &=\frac12\left(\frac{n(n+1)(2n+1)}6+\frac{n(n+1)}2\right)\\ &=\frac1{12}\Big(n(n+1)(2n+1)+3n(n+1)\Big)\\ &=\frac{n(n+1)}{12}(2n+4)\\ &=\frac16n(n+1)(n+2)\\ &=\binom{n+2}3\;, \end{align*}$$

so

$$\begin{align*} x&=\frac1{\binom{n+2}3-1}\\ &=\frac6{n(n+1)(n+2)-6}\\ &=\frac6{n^3+3n^2+2n-6}\\ &=\frac6{(n-1)(n^2+4n+6)}\;. \end{align*}$$

share|improve this answer
    
Can't this be done combinatorially? –  Ishan Banerjee Feb 24 '13 at 17:20
    
@Ishan: Conceivably, but I don’t at the moment see such an argument. –  Brian M. Scott Feb 24 '13 at 17:50
add comment

This question can be solved in a different way. Your equation is equivalent to $1+\frac1x=\sum_{(i,j,k)\in A}1=|A|$

Where $A={(i,j,k)| 1\leq k \leq j\leq i\leq n }$

So,$|A|= ^nC_3 +2^nC_2+^nC_1$ This is because, we can choose 3 distinct i,j,k or distinct i with the same j and k, or distinct k with the same i and j, or i=j=k.

So we get $1+\frac1x=^nC_3 +2^nC_2+^nC_1=^{n+2}C_3$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.